A Cardiopulmonary Instructor's Perspective on a Standardized Patient Experience: Implications for Cardiopulmonary Physical Therapy Education. - Cahalin, Lawrence P; Markowski, Alycia; Hickey, Mary; Hayward, Lorna (Cardiopulmonary Physical Therapy Journal (American Physical Therapy Association, Cardiopulmonary Section), 2011)
Purpose: Standardized patients (SP) in Doctor of Physical Therapy (DPT) curricula are increasingly used for students to practice developing clinical reasoning, communication, and professional skills in an authentic learning environment. The purposes of this article are to: (1) describe an instructional model that synthesized SPs, Internet-based communities of practice, and reflection to teach clinical reasoning in DPT students; and (2) a cardiovascular and pulmonary physical therapy (CPPT) instructor's perspective on the educational process and student clinical skill development. Summary of Key Points: The model, employed in a course: 'Integrative Physical Therapy Practice,' enabled the instructor to document student clinical performance and reasoning during an SP interaction. For students, clinical reasoning was illuminated through the model's assessment process. Data collected through the assessment process provided important feedback to the instructor on classroom instructional effectiveness. Conclusions: Examination of student learning experiences enabled the instructor to consider: (1) key aspects of examination and management for persons with cardiovascular or pulmonary disorders, (2) methods for visualizing clinical reasoning, (3) the impact of teaching on student learning, and (4) strategies for teaching CPPT. More research is indicated to investigate pedagogy for the development of clinical reasoning in DPT students.